Kontribusi Brand Image Universitas Bina Nusantara terhadap Minat Sektor Industri Atas Alumni - Nursanti, Tinjung Desy; Masruroh, Masruroh; Adhikara, Cooky Tri (Journal the Winners: Economics, Business, Management, and Information System Journal, 2009)
Brand image is the existence of characteristic of a number of associations leading to unity of meaning, which ultimately determines general consumer reaction in providing assessments or responses to a brand. The marketing communication efforts by the company may be able to present a flexible technique in shaping consumer perceptions towards products and services offered to consumers and to help create image and attributes for users. From the eyes of the public as consumers, brand image is developed gradually, starting from the first appearance of the brand in the wider community, known, and perceived by the public. The industrial sector as users of academic products shall be more selective in their choices. One consideration to be taken into factor is that of an alumnus of a university with a trusted reputation. In this case, Binus University has an image as one of the leading private university in Jakarta. This study analyzes the brand image of Binus University for the industrial sector, related associations Binus University and how much is the spread of influence in order to get the picture of Â quality and popularity of Binus University in the minds of the industrial sectors.